Identification and characterization of two sesquiterpene synthase genes involved in volatile-mediated defense in tea plant (Camellia sinensis) - Liu, Guanhua (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.